(untitled) (Journal of Medical & Health Sciences Review, 2025)
The study was conducted to evaluate the occurrence of anemia in pregnant women in the antenatal wards of the selected hospitals in Faisalabad, Pakistan, in 2025. Anemia has been one of the most prevalent health problems in pregnancy around the world, especially in developing nations, such as Pakistan, where it has led to such complications as preterm birth, low birth weight, and the higher rates of maternal illness. Its major etiologic factors are iron deficiency, poor diet and poor prenatal care and the physiologic hemodilution by the natural enlargement of blood volume during pregnancy, which further reduces hemoglobin. Notwithstanding other awareness campaigns, the prevalence of anemia in Pakistan is still high, which explains that region-specific studies are necessary. In the given cross-sectional study, the data were gathered using the structured questionnaires including 200 pregnant women of the Medina Teaching Hospital that included data related to dietary habits, supplement intake, and obstetric history. The standard laboratory methods were used to determine hemoglobin levels and were classified as per the WHO guidelines. The outcome indicated that 62.3%. The study population was anemic and moderate anemia was the predominant, which was accompanied by mild and severe anemia and highest prevalence was observed during the third trimester. The factors that contributed to it involved poor iron intake, multiple pregnancies, low adherence to supplements, and infrequent antenatal visits. The research also concludes that anemia is a significant public health issue among pregnant women in Faisalabad and that greater attention should be given to maternal health programs aimed at frequent screening, nutritional education, and supplementation of iron-folic acid to minimize the risk factors.